Joint procurement by heterogeneous buyers - Isabel Helmrath; Matthias Hunold; Johannes Muthers (Johannes Kepler University of Linz, Department of Economics, 2022)
We analyze self- and joint procurement of countries with heterogeneous demand for a good offered by a price discriminating monopolist. We find that not only countries with low but also with high demand can benefit from committing to jointly procure equal quantities at a uniform price, even if the supplier is capacity constrained. Free-riding of outside buyers as well as too much heterogeneity of insiders make the buyer group unstable. Uniform price procurement without a quantity restriction is only stable with intra-group transfers. We relate our findings to the COVID-19 vaccine procurement of the European Union.
Keywords: C79; D42; L12; 330; joint procurement; group purchase; heterogeneous buyer group; vaccineprocurement; price discrimination